Asymmetric Knee Joint Loading in Post-Stroke Gait: A Musculoskeletal Modeling Analysis of Medial and Lateral Compartment Forces - Georgios Giarmatzis; Nikolaos Aggelousis; Marinos Marinidis; Styliani Fotiadou; Erasmia Giannakou; Evangelia Makri; Junshi Liu; Konstantinos Vadikolias (Biomechanics)
Background/Objectives: Stroke survivors often develop asymmetric gait patterns that may lead to abnormal knee joint loading and potentially increased risk of osteoarthritis. This study aimed to investigate differences in knee joint loading between paretic and non-paretic limbs during walking in individuals post-stroke. Methods: Twenty-one chronic stroke survivors underwent three-dimensional gait analysis. A modified musculoskeletal model with a specialized knee mechanism was used to estimate medial and lateral tibiofemoral contact forces during the stance phase. Statistical parametric mapping was used to identify significant differences in joint kinematics, kinetics, and contact forces between limbs. Stepwise regression analyses examined relationships between knee moments and compartmental contact forces. Results: Significant differences in knee loading were observed between limbs, with the non-paretic limb experiencing higher medial compartment forces during early stance (6.7–15.1%, p = 0.001; 21.9–30.7%, p = 0.001) and late stance (72.3–93.7%, p < 0.001), and higher lateral compartment forces were recorded during pre-swing (86.2–99.0%, p < 0.001). In the non-paretic limb, knee extensor moment was the primary predictor of first peak medial contact force (R2 = 0.573), while knee abductor moment was the primary predictor in the paretic limb (R2 = 0.559). Conclusions: Musculoskeletal modeling revealed distinct asymmetries in knee joint loading between paretic and non-paretic limbs post-stroke, with the non-paretic limb experiencing consistently higher loads, particularly during late stance. These findings suggest that rehabilitation strategies should address not only paretic limb function but also potentially harmful compensatory mechanisms in the non-paretic limb to prevent long-term joint degeneration.